2011
DOI: 10.1093/ndt/gfr032
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of glomerular endothelial cells by anti-moesin activity of anti-myeloperoxidase antibody

Abstract: The endothelial CXC chemokines, KC and MIP-2, contribute to infiltration of neutrophils in MPO-ANCA-associated vasculitis involving glomerulonephritis. The activation of glomerular endothelial cells by anti-MPO IgG appeared to directly involve a signaling through moesin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…Given the cross-reaction to moesin of anti-MPO antibody [8], we studied whether the binding of anti-MPO mAb to GEnCs increased with the treatment of HMGB1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the cross-reaction to moesin of anti-MPO antibody [8], we studied whether the binding of anti-MPO mAb to GEnCs increased with the treatment of HMGB1.…”
Section: Resultsmentioning
confidence: 99%
“…Nagao et al identified a cross-reactive molecule on mouse GEnCs, which could be recognized by anti-MPO antibody, termed moesin [8]. They assumed that moesin shares certain similar sequences with those on the N-terminal region of the MPO heavy chain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations